A night divided - Nielsen, Jennifer A. (New York : Scholastic Press, 2015)
When the Berlin Wall went up, Gerta, her mother, and her brother Fritz were trapped on the eastern side where they were living, while her father, and her other brother Dominic were in the West--four years later, now twelve, Gerta sees her father on a viewing platform on the western side and realizes he wants her to risk her life trying to tunnel to freedom.
School Library Journal, July 2015.
Publisher's Weekly, June 2015.
Booklist, August 2015.
Horn Book, April 2016.
Bulletin (Center for Children's books), December 2015.
Voice of Youth Advocates (V.O.Y.A.), October 2015.
Keywords: Families -- Germany -- Berlin -- Juvenile fiction; Families -- Germany (East) -- Juvenile fiction; Berlin Wall, Berlin, Germany, 1961-1989 -- Juvenile fiction; Berlin Wall, Berlin, Germany, 1961-1989 -- Fiction; Berlin Wall, Berlin, Germany, 1961-1989 -- Fiction; Berlin Wall, Berlin, Germany, 1961-1989 -- Fiction; Berlin (Germany) -- History -- 1945-1990 -- Juvenile fiction; Berlin (Germany) -- History -- 1945-1990 -- Fiction; Germany (East) -- History -- 20th century -- Fiction; Berlin (Germany) -- History -- Fiction; Germany (East) -- History -- Fiction; Berlin (Germany) -- History -- 1945-1990 -- Fiction; Historical fiction